Synthesis and Characterization of Co/Mo Bimetallic Nanocatalysts - Ali, S (David Publishing, 2011)
Cobalt/Molybdenum bimetallic nanocatalysts were prepared by wet impregnation method on alumina support. Samples were characterized using hydrogen temperature-programmed reduction (H2-TPR), transmission electron microscopy (TEM) and N2 adsorption-desorption analyses. Fischer-Tropsch synthesis (FTS) was carried out in a fixed-bed microreactor at 543 K and 1 atm, with H2/CO = 2 v/v and space velocity, SV=12 L/g•h. The physicochemical properties and the FTS performance of the bimetallic nanocatalysts were analyzed and compared with the monometallic cobalt and molybdenum nanocatalysts. H2-TPR analysis of cobalt nanocatalyst indicated three temperature regions at 490 οC (low temperature), 710 οC (medium temperature) and 820 οC (high temperature). The incorporation of molybdenum into cobalt nanocatalysts increased the percentage of species reduced at low temperature. It also increased the average size of metal nanoparticles and enhanced hydrogen chemisorptions but decreased the degree of reduction of bimetallic nanocatalysts compared to those of the monometallic nanocatalysts. Bimetallic nanocatalysts enhanced the %CO conversion in the FTS. Among the nanocatalysts studied, bimetallic nanocatalyst with the composition of 50Co:50Mo resulted in the highest %CO conversion (42.6%), while the %CO conversion was 28.3% and 24%, respectively for the monometallic cobalt and molybdenum nanocatalysts.